Sorghums of the Sudan: analysis of regional diversity and distribution - Grenier, Cécile; Bramel-Cox, P.J.; Dahlberg, J.; El Ahmadi, A.; Mahmoud, M.; Peterson, G.; Rosenow, D.; Ejeta, G. (2004)
Sorghum [Sorghumbicolor (L.) Moench] is a very important crop in the Sudan serving as a primary source of food, beverage, and total livelihood for millions of people in the country. The crop originated in the Northeast quadrant of Africa, and the Sudan is widely recognized as a major center of diversity. Although Sudanese sorghum germplasm has been assembled and stored over the last 50 years, careful analysis of this valuable germplasm has not been made. The objectives of this study were to assess phenotypic diversity and compare pattern of distribution among Sudanese sorghum landraces collected from different geographical regions. Phenotypic diversity among landraces was high, as expressed by the large range of variation for mean quantitative traits and the high (0.81) Shannon-Weaver diversity index. Landraces from Gezira-Gedarif tended to be shorter in stature, earlier in maturity and less sensitive to changes in photoperiod. They also had long, narrow and compact panicles that may result from adaptation to low rainfall and early adoption of mechanized farming practices. In contrast, taller and later maturing plant types characterized sorghums from Equatoria, most of which delayed their flowering in response to increased day-length. These sorghums included many genotypes with small and light kernels. Collections from Kassala showed a higher frequency of landraces with kernels that were more difficult to thresh. Landraces from Blue Nile tended to have greater agronomic eliteness with higher proportion of landraces with white kernels, poorly covered and that were easy to thresh. Sorghums from the Upper Nile tended to have loose panicles with poorly covered kernels that may result from adaptation to high rainfall of the Southern region. Although distinct distributions of types were represented by geographical origin, a high level of within-region diversity was present among all Sudanese sorghums.